Multibody simulation of a rope-driven automated people mover. (September 2018) - Bucchi, Francesco; Frendo, Francesco; Bavaresco, Federico; Conte, Giuseppe
In this paper, a multibody model of the automated people mover, PisaMover, is presented. PisaMover is a rope-driven small train, composed of a few cabins, which makes use of train-inspired bogies. The aim of the model was to support the design of the architecture of the suspensions and to select the proper characteristics of the elastic and damping elements in order to fulfill comfort needs of passengers and to resolve the constraints related to the layout of the vehicle and the guide-ways. For this purpose, attention was especially focussed on the definition of the railway path and the modeling of the forces of the supporting and guidance wheels. A simplified model of the rope was implemented, which neglects the rope elasticity and computes the rope force direction taking account of the different positions of the sheaves along the path. The multibody simulation allowed to select the most appropriate suspension system and to properly define the elastic and damping characteristics of the shock absorbers, with respect to the technical constraints. A modal analysis was performed, and several dynamic on-track simulations were carried out to infer the effect of dampers' design on the comfort of passengers. Within the validity of the simplifying assumptions, the multibody simulation also allowed to obtain a fairly good estimate of the loads necessary for the design of the main structural components.